THE ROLE OF NURSES IN LIVER DISEASE MANAGEMENT (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Liver diseases, ranging from hepatitis to cirrhosis, present complex challenges for healthcare systems globally. Nurses play a critical role in managing these conditions through patient education, monitoring, and holistic care. This article explores the specific responsibilities of nurses in liver disease management and highlights evidence-based practices to improve patient outcomes.